All Antimony Chalcogenide Tandem Solar Cell. Issue 4 (25th February 2020) - Zhang, Jianwang; Lian, Weitao; Yin, Yiwei; Wang, Xiaomin; Tang, Rongfeng; Qian, Chen; Hao, Xiaojing; Zhu, Changfei; Chen, Tao
Abstract : A proof‐of‐concept tandem solar cell using Sb2 S3 and Sb2 Se3 as top and bottom cell absorber materials is demonstrated. The bandgaps of Sb2 S3 and Sb2 Se3 are 1.74 and 1.22 eV, perfectly satisfying the requirement of tandem solar cells. The application of few‐layer graphene enables high transmittance and excellent interfacial contact in the top subcell. By controlling the thickness of the top cell for maximizing the spectral application, the tandem device delivers a power conversion efficiency of 7.93%, which outperforms the individually optimized top cell (5.58%) and bottom cell (6.50%). Mechanistical investigation shows that the tandem device is able to make up voltage loss in the subcells, which is a critical concern in the current antimony chalcogenide solar cells. This study provides an alternative approach to enhancing the energy conversion efficiency of antimony selenosulfide. Abstract : A proof‐of‐concept tandem solar cell with Sb2 S3 and Sb2 Se3 as subcells shows perfectly matched spectral utilization and delivers higher efficiency than the individually optimized subcells.